Cytotoxic chemotherapy and the evolution of cellular and viral resistance to antiretroviral therapy in HIV- infected individuals with lymphoma. Issue 5 (2nd September 2016) - McFaul, Katie; Liptrott, Neill; Cox, Alison; Martin, Phillip; Egan, Deirdre; Owen, Andrew; Kelly, Sarah; Karolia, Zeenat; Shaw, Kate; Bower, Mark; Boffito, Marta
Abstract : Background: The use of combination antiretroviral therapy (cART) and cytotoxic chemotherapy for HIV-associated lymphoma runs the risks of inducing HIV drug resistance. This study examined two possible mechanisms: altered expression of membrane drug transporter protein (MTP) and acquisition of mutations in pro-viral DNA. Methods: Expression levels of MTP and pro-viral DNA resistance mutation analysis were performed on peripheral blood mononuclear cells (PBMC) before, during, and after chemotherapy. Results: Twenty nine patients completed the three time point estimations. There were no significant variations before, during, and after chemotherapy in the expression of four MTPs: ABCB1, ABCC1, ABCC2, and SLCO3A1 (OATP3A1). Pro-viral DNA sequencing revealed that only one patient developed a new nucleos/tide reverse transcriptase inhibitor-associated mutation (184V) during the course of the study, giving a mutation rate of 0.0027 per person per year. Conclusions: In conclusion, concomitant administration of cytotoxic chemotherapy and cART does not induce expression of MTP. Furthermore, no significant changes in viral resistance were observed pre- and post-chemotherapy, suggesting mutagenic cytotoxic chemotherapy seems not to induce mutations in HIV pro-viral DNA.